Ultrastructural Dendritic Changes Underlying Diaschisis After Capsular Infarct. Issue 5 (25th February 2020) - Lee, Min-Cheol; Kim, Ra Gyung; Lee, Taebum; Kim, Jo-Heon; Lee, Kyung-Hwa; Choi, Yoo-Duk; Kim, Hyung-Seok; Cho, Jongwook; Park, Ji-Young; Kim, Hyoung-Ihl
Abstract: Diaschisis has been described as functional depression distant to the lesion. A variety of neuroscientific approaches have been used to investigate the mechanisms underlying diaschisis. However, few studies have examined the pathological changes in diaschisis at ultrastructural level. Here, we used a rat model of capsular infarct that consistently produces diaschisis in ipsilesional and contralesional motor and sensory cortices. To verify the occurrence of diaschisis and monitor time-dependent changes in diaschisis, we performed longitudinal 2-deoxy-2-[18 F ]-fluoro-d -glucose microPET (FDG-microPET) study. We also used light and electron microscopy to identify the microscopic and ultrastructural changes at the diaschisis site at 7, 14, and 21 days after capsular infarct modeling (CIM). FDG-microPET showed the occurrence of diaschisis after CIM. Light microscopic examinations revealed no significant histopathological changes at the diaschisis site except a mild degree of reactive astrogliosis. However, electron microscopy revealed swollen, hydropic degeneration of axial dendrites and axodendritic synapses, although the neuronal soma (including nuclear chromatin and cytoplasmic organelles) and myelinated axons were relatively well preserved up to 21 days after injury. Furthermore, number of axodendritic synapses was significantly decreased after CIM. These data indicate that a circumscribed subcortical white-matter lesion produces ultrastructural pathological changes related to the pathogenesis of diaschisis.